ASTHMA IN CYSTIC FIBROSIS - Marcela Daniela Ionescu; Ioana-Alina Anca; Mihaela Balgradean (Amaltea Medical Publishing House, 2015)
Cystic fi brosis (CF) is the most common autosomal recessive disease in Caucasians. Lung disease is characterized by impaired mucocilliary clearance with airway obstruction and chronic pulmonary infection and infl ammation. Wheeze is a common symptom in CF, but in some cases the wheeze is due to the presence of concomitant asthma. There is no consensus on how to defi ne CF asthma, but the diagnosis is predominantly based on the patient's strong family and personal history of atopy.